The perspectives of older women with chronic neck pain on perceived effects of qigong and exercise therapy on aging: a qualitative interview study - Holmberg, Christine (Dove Medical Press, 2014)
Chronic pain is prevalent in elderly populations. The goals of this study were 1) to understand the results of a randomized clinical trial – Qigong and Exercise Therapy for Elderly Patients with Chronic Neck Pain (QIBANE) – that showed no difference between qigong, exercise therapy, and no-treatment on quality of life, and 2) to understand how elderly individuals with chronic pain experience interventions of qigong and exercise therapy. A qualitative interview study was conducted with 20 QIBANE participants. Interviews asked about motivation for and expectations of trial participation, experiences with the exercise classes (qigong or exercise therapy), and changes in pain experience. Interviews were transcribed, entered into the software program ATLAS.ti, and coded thematically by two coders. Content analysis was performed. All interviewees reflected positively on their QIBANE experience and described their participation in QIBANE as helpful. However, what was discussed in both groups when they talked about “positive experiences” in the study differed between the two groups. For example, themes that emerged in the exercise-therapy group related to difficulties associated with aging and staying physically active. In the interviews with qigong group members, emergent themes related to qigong as a method that improved bodily experiences and influenced daily activities. The effects that exercise therapy and qigong have on an elderly population cannot be captured by health-related quality-of-life measurements, such as the Short Form (36) Health Survey. Broader concepts of quality of life that include the concepts of self-efficacy and positive affect may be more appropriate. The results presented in this study suggest that for this population group, the approach of patient-centered outcomes is especially pertinent in order to design meaningful intervention studies in the elderly. This means that research questions, interventions, and outcome measurements need to take into account the special situation of elderly people.